To the question of the relevance of modern comparative research - G. P. Podolian, (Ukrainian Cultural Studies, 2019)
The article analyzes the relevance of comparative research in the modern conditions of the global world. The forms of communication that are immanent for any culture, the development of another's experience of cultural being, intercultural interactions are determined. The significance of philosophy is deter- mined as one of the foundations contributing to the processes of forming dialogism as a cultural characteristic of ancient, and then Western culture.The culture-creating nature of the communicative, dialogical nature of Western culture is interpreted as an important basis for the emergence of a comparative historical method of studying cultural diversity. Attention is focused on the productive experience of cultural interaction that emerged in ancient Greece and developed by further followers in the Western world. The history of the development of the comparative tradition is traced through the delineation of the main factors, which, in their entirety, have become a favorable basis for the emergence of systemic research using the comparative method. Indicates the main trends of modern comparative searches and unsolved problems. The directions of the heuristic development of the future prospects of this method of cultural analysis are indicated. These include: a high level of dialogicity of ancient, and then Western culture; geographical discoveries of the New time; educational and cultural activities of representatives of the Enlightenment; the development of scientific knowledge in the direction of the penetration of ideas about the natural movement of social development from the natural sciences into the social sciences; the appeals and popularization of O. Conte of studying the "main laws" of social phenomena, including the comparative historical method; authoritative recognition of history and linguistics as a science in the nineteenth century; the idea of progressive progress of human culture; scientific activities of representatives of cultural schools of evolutionary anthropology, diffusionism, social anthropology.
Keywords: comparative historical method, comparative method, comparative studies, comparative studies, dialogue, communication